Institution reinforcement of mosque in social economic empowerment of small traders community - Alfiana Yuli Efiyanti; Muhammad Ali; Saiful Amin (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2021)
Historically, mosque is the center for human civilization with various activities covering social, economy, and culture. However, its function have been shifted and specialized into a place of worship.  This paper aims to describe the contribution of the great mosque of Attaqwa Pancor in social economic empowerment, particularly small businesses in Pancor, East Lombok, Nusa Tenggara Barat (NTB). The Data are collected through observation, interview, and document study. The result of the analysis shows that mosque involvement in the small-scale economic activities has brought them to be free from the difficulty of capital access and dependence. In the first stage, that is the period of 2019 to August 2020, through Mawar Emas program, total of 80 small-traders in Pancor village was helped to be free from debt problems. The great mosque of Attaqwa which is supported by Indonesia Sharia Economic Community (Masyarakat Ekonomi Syariah, MES) were successfully distributing the total amount of 80 million rupiahs for the small business purposes. The existence of the Attaqwa mosque proves and affirms that religious institutions can contribute to the social economic development. Considering the strategic position, this paper suggests the need for institutional reinforcement of mosque to restore its broad role in addition to religious issues.JEL Classification:  A13; O15; Z12